0250 Synthetic Cubism at War: New Necessities, New Challenges - Belén Atencia Conde-Pumpido (RIHA Journal, 2020)
When we talk about the Synthetic Cubism period, what exactly are we referring to? What aesthetic possibilities and considerations define it insofar as its origin and later evolution are concerned? To what extent did the disorder that the Great War unleashed, with all its political, sociological and moral demands, influence the reformulation of a purely synthetic syntax? This article attempts to answer these and other questions relating to the sociological-aesthetic interferences that would influence the Parisian Cubist style of the war years, and in particular the works of Juan Gris, María Blanchard, Jacques Lipchitz and Jean Metzinger during the spring and summer that they shared with one another in 1918, until it consolidated into what we now know as Crystal Cubism.